If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 600 = n Solving 600 = n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 600 + -1n = n + -1n Combine like terms: n + -1n = 0 600 + -1n = 0 Add '-600' to each side of the equation. 600 + -600 + -1n = 0 + -600 Combine like terms: 600 + -600 = 0 0 + -1n = 0 + -600 -1n = 0 + -600 Combine like terms: 0 + -600 = -600 -1n = -600 Divide each side by '-1'. n = 600 Simplifying n = 600
| 3h^2+7h-6=0 | | -32z=-64 | | j+w=r | | 7x+42=49 | | 60x^3-150x=0 | | 15-7=14z+12 | | y-0=7 | | z-28=6 | | -490t^2+1470t=980 | | 2x(7)=352 | | -2/5x-6-5 | | 5-0.05x=3 | | .000036-.00072x=x^2 | | -490t+1470t=980 | | -1.5(4-r)=-12 | | -8x+2y=6 | | 4775.94=2r*3.14 | | 2/5=10/m | | 90x^2+x+1=0 | | 16/9=32/n | | 2h^2-h-78=0 | | 10x^2-45x-1000=0 | | X(3X+4)=95 | | 3x^2+7x-21=2x+7 | | .2m-8=-6 | | 18/24=27/n | | .25(8-4p)+2p=12 | | 2h^2=3h | | (4x^2-22x-42)(x-7)=0 | | w^2-2w=99 | | x/20=900/30 | | 90x^2+x-91=0 |